A Roda da Fortuna nos Dictats de Ausiàs March (c. 1397-1439). - DA COSTA, RICARDO; LEMKE, WILSON COIMBRA (Scripta)
The allegory of the Wheel of Fortune is a recurring theme in medieval thought, especially in Philosophy and Literature. The notion of fortune was inherited from a double tradition and adapted by Ausiàs March (c. 1397-1439) for literary use. The first source is ancient: Greco-Roman. First, Aristotle (384-322 BC) began to find a place for it in his philosophical and political conception (Physics, II, 4-6; Politics, V, 3). Afterwards, Polybius (200-120 BC), Livy (c. 59 BC - 17 AD) and Plutarch (46 - 120) analyzed its influence on history. The second, medieval, is the Consolation of Philosophy, by Boethius (c. 477-524). We will deal with this allegory in the Dictats, by Ausiàs March, to show how the Valencian poet literarily developed the theme of the instability of the Wheel of Fortune in his poems.